COVID-19 vaccination in pregnant and lactating women - Kaziród, Karolina; Kuryło, Weronika; Brzuszkiewicz, Kinga; Miturski, Andrzej; Semczuk-Sikora, Anna (Journal of Education, Health and Sport, 2022)
Introduction: The COVID-19 pandemic significantly changed the lifestyle of pregnant women. Pregnant women with COVID-19 are more likely to suffer from severe disease, as well as unfavorable pregnancy and childbirth. Currently, there is no causal treatment for this disease available, so attention should be paid to preventing infection with vaccines. Aim of the study: A review of the literature on the influence of COVID-19 vaccines on the course of pregnancy and summary of recommendations regarding the use of COVID-19 vaccines during pregnancy and breastfeeding. State of knwoledge: Three types of COVID-19 vaccines are most commonly used: mRNA vaccines, vector vaccines as well as subunit vaccines. In preclinical developmental and reproductive toxicity studies in animal models, there were no alarming safety signals, and observations of vaccinated pregnant women did not reveal any complications with respect to the course of pregnancy and development of the fetus. No cases of neonatal death have been reported in the first 28 days after birth. Most of the side effects following vaccination, such as injection site pain or tenderness, fatigue, fever or muscle pain, were moderate and resolved within 24 hours. The current research results confirm a positive immune response in pregnant women. Moreover, it is important that the presence of antibodies in the umbilical cord blood makes it possible to protect and reduce the risk of SARS-CoV-2 infection of the newborn. Summary: All pregnant women, irrespective of trimester, and breastfeeding mothers are advised to administer a booster dose of the COVID-19 vaccine within an appropriate period of time after the primary vaccination schedule.